Charitable organizations as a new visible source of support for older people during the COVID-19 pandemic in Russia - Elena, Golubeva (Magyar Gerontológia, 2023)
The activities of a third sector including non-governmental organizations (NGOs), charity foundations, and voluntary associations have received a new impetus during the COVID-19 pandemic their roles in supporting older people much widened compared to the time before the pandemic (Zobernyus et al. 2022).